IMPLEMENTATION OF CURRICULUM 2013 AT SOCIAL STUDIES SUBJECT IN ISLAMIC PUBLIC SECONDARY SCHOOL OF MALANG 1 - Afifah, Silvi Nur (JURNAL PENDIDIKAN ILMU SOSIAL, 2017)
This study aims to determine the implementation of curriculum 2013 on subjects integrated Social Science in Malang 1 Islamic Public Junior High School. The research method used in this study is a qualitative approach with descriptive method. Collecting data has done through observation, interview and documentation study. The results showed that in general the implementation of Curriculum 2013 on Social Science subjects in Malang 1 Islamic Public Junior High School using an integrated scientific approach. Social Science teachers are still experiencing some obstacles and adjust to the real conditions in the field. This is evidenced in implementing learning Social Science teachers already using a scientific approach, but most of the integrated Social Science only occurs in the classroom so do not provide concrete learning experiences for students.